2022
DOI: 10.3949/ccjm.89a.21032
|View full text |Cite
|
Sign up to set email alerts
|

Stellate ganglion block as a treatment for vasomotor symptoms: Clinical application

Abstract: V asomotor symptoms (vms), also called hot fl ashes, hot fl ushes, and night sweats, are common symptoms of menopause. 1 They are described as moments of intense heat, usually accompanied by sweating and fl ushing in the upper body, including the head, neck, and upper torso, 1 and they are associated with poor health outcomes and decreased quality of life. While hormonal therapies are the mainstay of treatment for VMS, there is a clear need for safe and effective nonhormonal treatment options for women who cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…While HRT continues to be the first-line option for VMS, in patients with refractory symptoms or contraindications, SGB is a promising alternative. Limitations include potentially higher cost, lack of availability, and more of the procedure [ 56 ].…”
Section: Reviewmentioning
confidence: 99%
“…While HRT continues to be the first-line option for VMS, in patients with refractory symptoms or contraindications, SGB is a promising alternative. Limitations include potentially higher cost, lack of availability, and more of the procedure [ 56 ].…”
Section: Reviewmentioning
confidence: 99%
“…While hormone therapy is demonstrably effective for vasomotor symptoms for the vast majority of perimenopausal and postmenopausal women, for some patients it is not an acceptable choice. In this issue of the Journal, Lee et al 1 discuss stellate ganglion block (SGB), the guided percutaneous injection of anesthetic to relieve vasomotor symptoms, as an alternative in women for whom estrogen replacement is not a good option or has failed along with other approaches to provide adequate symptom control.…”
Section: Potential Systemic Benefi Ts Of Shocking or Blocking Nervesmentioning
confidence: 99%
“…123 By administering a local anesthetic such as lidocaine under fluoroscopic and ultrasonographic guidance, SGB has been used for the past 50 years as a targeted treatment for pain syndromes such as migraine, upper extremity and upper body pain, as well as complex regional pain syndromes. 124 While data show that SGB may improve VMS, the mechanism is unclear. Several small studies have shown that, whether approached unilaterally or bilaterally, SGB reduces hot flash severity by 45% to 90% in about 4–24 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…123 Most studies reported no significant adverse events, although there are rare risks associated with the injection itself. 124 These complications can include damage to the surrounding areas, such as the vasculature, neural tissue, esophagus, or trachea. 124 Risk of complications can be mitigated with imaging guidance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation